Poorly Controlled Type 3c Diabetes due to Use of Veterinarian Insulin Syringes - Francisco Barrera; Natia Murvelashvili (Case Reports in Endocrinology)
Initiation of insulin therapy can be challenging for patients; proper training should be given by physicians and certified educators to ensure correct and safe use for outpatient population. Different insulin strengths are now available in the US; while U-40 insulin does not exist in the United States for humans, it is a very common strength used in animals. We are reporting a 30-year-old male that became insulin dependent after hospitalization for necrotizing pancreatitis who was using U-40 syringes to draw from the prescribed insulin U-100 and also presented with repeated hypoglycemic episodes.